Scalable photonic quantum networks - Walmsley, I; Nunn, J; Barbieri, M; Kolthammer, S; Xin, X; Datta, A; Michelberger, P; Sprague, M; Champion, T; Spring, J; Metcalf, B; Humphreys, P (2013)
A scalable photonic quantum network will facilitate the preparation of distributed quantum correlations among many light beams, allowing a new regime of state complexity to be accessed, and enabling new quantum-enhanced applications. Such a network can be constructed by means of linear optical operations on pure-state quantum light beams, measurement by efficient photodetectors, and storage in a photonic quantum memory. © OSA 2013.